Keterampilan Tata Boga Bagi Siswa Autis di SMK Inklusif Kota Bandung - Muhaimi Mughni Prayogo (PLD UIN Sunan Kalijaga, 2019)
The vocational independence of autistic students can be achieved if the skills learning program is based on the potential and needs of students. Unfortunately, learning culinary skills for autistic students in an inclusive vocational school in Bandung has not been adjusted so that student achievement is not seen. This is a research and development study using ADDIE model in developing a culinary skill learning program for autistic students at the school. The subject of the study was a Class X autistic student, at the Department of Catering. Program development begins with assessment, curriculum analysis, making alignment programs, then making individual learning programs. Functional learning plans are made for three basic subjects: Hygine Sanitation and Work Safety, Food Knowledge, and Basic Food.[Kemandirian vokasional siswa autis dapat tercapai apabila program pembelajaran keterampilan disusun berdasarkan potensi dan kebutuhan siswa. Sayangnya, pembelajaran keterampilan tata boga bagi siswa autis di salah satu SMK inklusif di Kota Bandung belum disesuaikan sehingga prestasi belajar siswa tidak terlihat. Penelitian ini berjenis research and development yang menggunakan model ADDIE untuk mengembangkan program pembelajaran keterampilan tata boga bagi siswa autis di sekolah tersebut. Subjek penelitian adalah seorang siswa autis Kelas X, Jurusan Tata Boga. Pengembangan program diawali dengan asesmen, analisis kurikulum, pembuatan program penyelarasan, kemudian pemembuatan program pembelajaran individual. Rencana pembelajaran fungsional dibuat untuk tiga mata pelajaran dasar: Sanitasi Hygine dan Keselamatan Kerja, Pengetahuan Bahan Makanan, dan Boga Dasar]